Euglycemic DKA (euDKA) as a presentation of COVID‐19. Issue 1 (20th November 2020) - Dass, Bhagwan; Beck, Andrew; Holmes, Cody; Morton, Glenville
Abstract: COVID‐19 in the setting of SGLT2 inhibitor use may precipitate euglycemic DKA separate from known acute viral illness and dehydration precipitants. There should be consideration of proactive discontinuation of these medications in these patients. Abstract : COVID‐19 in the setting of SGLT2 inhibitor use may precipitate euglycemic DKA separate from known acute viral illness and dehydration precipitants. There should be consideration of proactive discontinuation of these medications in these patients.